PERAN GURU SEBAGAI MOTIFATOR DALAM PEGEMBAGAN PESERTA DIDIK DI SDN NEGLASARI - Ujang Jamaludin; Reksa Adya Pribadi; Hana Sela Ijie (STKIP Subang, 2023)
The responsibility of teachers is to help students to develop their maximum potential. The purpose of this study is to describe the role of teachers as motivators to develop the potential of students who must develop at SDN Neglasari Cicare, Serang City Province. Banten, not only dealing with intelligence and skill problems, but rather covering all aspects of personality. That is, students are difficult to participate in learning to overcome the lack of discipline of students, teachers often guide and advise students during the learning process The task of the teacher is not only to guide students, but the task of a teacher must be able to build a comfortable learning atmosphere in the classroom so that students can receive learning well. This research method uses qualitative descriptiveness. Lokasih this research at SDN Neglasari cipare, Serang City Prov. Bantam . The primary data sources used include homeroom teachers in class III, data collection techniques used are observation, interviews and documentation.data collection techniques are by using evidence sources, data reduction, data presentation, conclusion drawing